Komposisi Jenis dan Tingkat Trofik (Trophic Level) Hasil Tangkapan Bagan di Perairan Desa Ohoililir, Kabupaten Maluku Tenggara - Erna Almohdar; Fabian N. J Souisa (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2017)
An effort to maintain biodiversity of species in ecosystem is essential considering the high demand of fish in the market which is related to the amount of exploration. Trophic level is position of a species or a group of species within a food chain or food web, where it showed phases of transfer energy and material inter and intra on each group. This study aimed to analyze species composition and trophic level of lift net catch in ohoililir village water, southeast maluku regency. Observation variables on this research were, species composition, length and weight of fish also trophic level of catch by using lift net. Experimental fishing was the methodology for data collecting. Results shows that, trophic level of fish which catch by lift net was categories included to trophic level three (TL3), means most of fish catch by lift net dominated by omnivorspecies, as the result the fish structure community and pyramid become unstable. In order to prevent this matter, better conservation of fish around the area based on trophic level by considering various ecosystem components like fish and its food chain.